Special Education Teachers Task Load In Malaysia: A Review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The workload of special education teachers occurs when teachers take on a variety of tasks, whether related to special education or not in a given time. Special education teachers at PPKI have to perform tasks that are not related to MBK in the time they are supposed to teach MBK. Many researchers state that the workload of special education teachers is the tasks borne affecting their primary role in teaching MBK. The researchers also explained that the workload of special education teachers made teachers feel dissatisfied in their teaching of MBK. This study was conducted to review previous articles that discuss the issue of workload of special education teachers. The findings of this study are expected to be able to provide a clear picture to future researchers related to the issue of teacher workload.